A Call for Integral Violence Studies. (March 2021) - Davenport, Christian
The legacies of racial violence are generally understudied and thus not well understood. Extant academic work on the topic generally focuses on a specific form of contention like war or rebellion as well as specific consequences like economic development or voting. I use insights from a global evaluation of the political and economic consequences of contention to identify the pitfalls of this typical approach and argue for an alternative that I call integral violence studies : a comprehensive approach that brings together the best that social sciences and humanities have to offer in an effort to understand legacy effects.